2013
DOI: 10.1074/jbc.m112.434498
|View full text |Cite
|
Sign up to set email alerts
|

The N-terminal Region of the DNA-dependent Protein Kinase Catalytic Subunit Is Required for Its DNA Double-stranded Break-mediated Activation

Abstract: Background:The Ku70/80-DNA complex recruits DNA-PKcs to DSBs and results in activation of DNA-PKcs kinase activity. Results: Truncation fragments of DNA-PKcs show that different regions of the protein are required for complete functionality of DNA-PKcs. Conclusion:The N-terminal region of DNA-PKcs is required for its ability to interact with the Ku-DNA complex and its full activation. Significance: We provide insights into the biochemical mechanism required for DNA-PKcs activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 57 publications
1
29
0
Order By: Relevance
“…Contrary to the paradigm that binding to DNA is a requirement for DNA-PKcs activation, it was demonstrated that DNA-PKcs autophosphorylation can be modulated by N-terminal conformational changes in the protein (such as that likely caused by DNA binding) [52]. This supposition was further supported by findings which revealed that the N-terminus (but not the C-terminus) is required for binding to the Ku-DNA complex and robust DNA-PKcs activity [53]. These collective studies support the concept that the N-terminus of DNA-PKcs is crucial for both targeting to Ku-bound DNA, and for conformational change-induced enzymatic activity.…”
Section: Regulation Of Dna-pk Activitymentioning
confidence: 99%
“…Contrary to the paradigm that binding to DNA is a requirement for DNA-PKcs activation, it was demonstrated that DNA-PKcs autophosphorylation can be modulated by N-terminal conformational changes in the protein (such as that likely caused by DNA binding) [52]. This supposition was further supported by findings which revealed that the N-terminus (but not the C-terminus) is required for binding to the Ku-DNA complex and robust DNA-PKcs activity [53]. These collective studies support the concept that the N-terminus of DNA-PKcs is crucial for both targeting to Ku-bound DNA, and for conformational change-induced enzymatic activity.…”
Section: Regulation Of Dna-pk Activitymentioning
confidence: 99%
“…DNA double-strand breaks (DSBs) 1 occur frequently during cell cycle progression and are corrected either by non-homologous end joining (NHEJ) or homologous recombination (HR). DNA-dependent protein kinase (DNA-PK) plays a key role in NHEJ-mediated repair of DSBs, and is comprised of a DNAbinding heterodimer Ku70/Ku80 and a catalytic subunit (DNAPKcs) that are necessary for the kinase activity of the enzyme (45). Euchromatin DSBs are repaired by NHEJ during G 1 and G 2 phase, whereas heterochromatin DSB repair is mediated by HR during G 2 phase (46,47), and perhaps also during S phase (48).…”
Section: Mass Spectrometric Identification and Quantification Of Thementioning
confidence: 99%
“…DNA-PKcs is composed of HEAT (Huntington-elongation-A-subunit-TOR) repeats in its N-terminus, which produce a pincer-shaped structure that forms a central channel and a C-terminal region that contains the PI3 kinase domain, which is flanked by the FAT (FRAP, ATM, TRRAP) domain at its N-terminal side and by the FATC domain at its C-terminal side [5, 6]. Following DSB induction, the Ku heterodimer quickly binds to the DSB ends and recruits DNA-PKcs to the break site, which is mediated by the N-terminal region of DNA-PKcs [79]. Upon interacting with the DSB-Ku complex, DNA-PKcs is activated.…”
Section: Introductionmentioning
confidence: 99%